2017
DOI: 10.1080/2156857x.2017.1310128
|View full text |Cite
|
Sign up to set email alerts
|

Expressing and responding to self-efficacy in meetings between clients and social work professionals

Abstract: Self-efficacy is a pivotal element when the long-term unemployed are to increase their chances of labour market participation, making the ways in which clients' beliefs in their capabilities are reflected in the delivery of public employment services particularly relevant. While existing research has pointed to the importance of both meetings with social services and self-efficacy for return to work, little knowledge exists on how self-efficacy is managed in these meetings. However, if social work professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…In a study from North America, Tilson and Simonsen (2013) show how successful work-related support for vulnerable young people is characterised by a genuine confidence in these young people's abilities, an awareness of their life context and an ability to communicate with them and their families. A Danish study also describes the social workers' ability to build users' selfefficacy as crucial for their success in returning to work (Danneris & Dall, 2017).…”
Section: Building Relationshipsmentioning
confidence: 99%
“…In a study from North America, Tilson and Simonsen (2013) show how successful work-related support for vulnerable young people is characterised by a genuine confidence in these young people's abilities, an awareness of their life context and an ability to communicate with them and their families. A Danish study also describes the social workers' ability to build users' selfefficacy as crucial for their success in returning to work (Danneris & Dall, 2017).…”
Section: Building Relationshipsmentioning
confidence: 99%
“…Studying institutional interactions reveals that even resistance can be a very active and productive force in meetings between SLBs and clients (Juhila et al, ). Recent studies have showed that when it comes to gradual progression toward labor market participation for the vulnerable unemployed clients, one of the most important elements is that the both the client and the SLB believe that labor market participation is a possibility (Danneris & Dall, ; Danneris et al, ; Rosholm et al, ).…”
Section: Looking At How Policy Is Implemented Though Talkmentioning
confidence: 89%
“…The analytical focus of this article will thus be on communicative practices in the interaction between SLBs and clients paying specific interest to the ways in which SLBs mediate and translate policy targets such as getting the clients to focus on (the possibility of) labor market participation. While the policy area of welfare‐to‐work has been heavily evaluated, the communicative and in situ practice of the SLBs have rarely been studied, albeit with some exceptions (Boehringer & Ute, ; Caswell, Eskelinen, & Olesen, ; Danneris & Dall, ; Eskelinen et al, ; Toerien et al, ). Eskelinen and Olesen () have analyzed small narratives on how vulnerable the unemployed saw themselves in relation to the labor market.…”
Section: Looking At How Policy Is Implemented Though Talkmentioning
confidence: 99%
“…Drew et al, 2010;Irvine et al, 2010;Toerien et al, 2015;Hansen and Natland, 2017) and the unemployed individuals (e.g. Solberg, 2011aSolberg, , 2011bSolberg, , 2014Danneris and Dall, 2017) as co-producers of how policy measures are implemented. These micro-level studies demonstrate the contingent and negotiated nature of how policy is executed in practice.…”
Section: Researching the Front-line Of Wtw Bureaucraciesmentioning
confidence: 99%